Improved critical current density in ex situ processed MgB2 tapes by the size reduction of grains and crystallites by high-energy ball milling. (March 2017) - Fujii, Hiroki; Ishitoya, Akira; Itoh, Shinji; Ozawa, Kiyoshi; Kitaguchi, Hitoshi
Highlights: MgB2 crystallite size decreases to half of the previous reported by ball milling. The ball milling process lowers the processing temperature of ex situ MgB2 tapes. Size reduction of crystallites and grains doubles the J c performance of the tapes. Abstract: We have fabricated Fe-sheathed MgB2 tapes through an ex situ process in a powder-in-tube (PIT) technique using powders ball milled under various conditions. Although the ex situ processed wires and tapes using the high-energy ball milled MgB2 powders have been studied and the decrease of grain and crystallite sizes of MgB2 and the critical current density ( J c ) improvement of those conductors were reported so far, the use of filling powders milled at a higher rotation speed than previously reported further decreases the crystallite size and improves the J c properties. The improved J c values at 4.2 K and 10 T were nearly twice as large as those previously reported. Those milled powders and hence as-rolled tapes easily receive contamination in air. Thus, the transport J c properties are easily deteriorated and scattered unless the samples are handled with care. The optimized heat treatment temperature ( T opt ) of those tape samples at which best performance in the J c property is obtained decreases by more than 100 °C, compared with that of tapes using the as-received MgB2 powder.